Sintesis dan Uji Aktivitas Antibakteri Senyawa N-Fenil-4-Bromobenzamida (Synthesis and Antibacterial Activity Assay of N-Phenyl-4-Bromobenzamide) - Nazilatul Maghfiroh; Indah Purnama Sary; Dwi Koko Pratoko (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Infectious diseases are contagious disease caused by pathogenic microorganisms and can be spread directly or indirectly from one person to another. The aim of this research was to synthesized N-phenyl-4-bromobenzamide as a new antibacterial agent. Thereaction was carried out by reacting 1,3-diphenylthiourea with 4-bromobenzoyl chloride by nucleophilic substitution. The purification of this compound was confirmed by TLC and the structure was identified by UV, IR, 1H-NMR and 13C-NMR. The newly synthesized compound was screened for its antibacterial activity against gram-positive and gram-negative bacteria, Staphylococcus aureus ATCC 6538 and Pseudomonas aeruginosa ATCC 27853 using well diffusion method. The concentration of the test solution used were 31.25; 62.5; 125; 250; 500; 1,000; 2,000; 4,000; 8,000; and 10,000 μg/ml with levofloxacin as positive control. The synthesized product did not show any antibacterial activity which characterized by the absence of inhibition zone.Keywords: 1,3-diphenylthiourea, N-phenyl-4-bromobenzamide, nucleophilic substitution, antibacterial activity.